Effects of 5- fluorouracil and mitomycine-C on glaucoma filtration surgery in rabbits - Kılıç, Servet; Girgin, Aydın (My University, 2002)
The purpose of this study was to examine the effects of 5-fluorouracil (5-FU) and mytomycine-C (MMC) on the success rate of glaucoma filtration surgery (GFS). A superior fornix-based conjunctival flap was created on the right eyes of 12 rabbits divided randomly into three equal groups termed groups 1, 2 and 3. After a small piece of sponge soaked with balanced salt solution (BSS) in group 1 (control), 5-FU (50 mg/ ml) in group 2 and MMC (0.02 mg/ ml) in group 3 was kept on the filtration sites for 5 minutes, the filtration fistula (sclerectomy) was performed and the flap was replaced. Postoperatively, BSS, 5-FU and MMC with doses of 0.1 ml were injected 4 times with certain intervals into the inferior fornixes of the same groups. The presence of the corneal edema, neovascularization and defect, appearance of the filtering bleb, states of the aqueous humor, iris, lens and changes in intraocular pressure (IOP) were observed. In one case, severe conjunctival hyperemia associated with the corneal flush and hyphema was determined. A mild corneal edema in half the members of group 1, and all the members of groups 2 and 3, was found. The IOP, which reduced sharply in all cases immediately after the GFS, reached its preoperative level approximately in 14, 28 and 51 days in groups 1, 2 and 3, respectively. There was a significant difference (P<0.001) both within and between the groups regarding the survival rate of the filtering fistula. The duration of failure of the filtration bleb was also found to be short in group 1 when compared with group 2 and in group 2 when compared with group 3. In conclusion, the success rate of the GFS was determined to be significantly higher (P<0.001) in MMC than 5-FU and in 5-FU than in the control. Additionally, it was observed that both MMC and 5-FU produced no persistent adverse effects on the eye tissues.
Keywords: Surgery; intraocular pressure; glaucoma; rabbits; filtration surgery; fluorouracil; mitomycin